ON MODELLING LOCAL LOOPS FOR DIGITAL SUBSCRIBER LINE (DSL) - Xuân, Nguyễn Đình; Minh, Hoàng; Anh, Nguyễn Thuý (Vietnam Journal of Science and Technology, 2012)
ABSTRACT This paper is posed on the single point subscriber line modeling problem, consisting of two main paragraphs out of the one for introduction and of that for remarks and suggestions for next works. In the second paragraph, a brief report is made on network topology and characteristics of local loop model obtaining from transmission line theory and electrical characteristics of twisted pair segments. Being of distributed nature, parameters of local loop models are not found to be successfully estimated by common techniques with the use of direction time response (TDR) in system identification theory. However, two algorithms well known on the basis of method of direction estimate (MODE) namely MODE-WRELAX and MODE-type are briefly resumed in the second paragraph. In the third one, a method is proposed on the basis of two dimensional Poisson Momentum Function which transforms signals on the both sides of the system, i.e. input and output sides, to spatial-time domain for direction -of-arrival estimation. The fact behind the spatial-time domain is that time-frequency space leading to the usage of MODE-type algorithm for separation of different reflections in frequency domain. In the last paragraph, three different comments on the proposed method of supplying measurements data by Poisson Momentum Function for estimation purpose and suggestions for further study to be carried out.